Tissue doppler echocardiography as a predictor of early subclinical right ventricular diastolic dysfunction in asthmatic children - Ahmed Mohammad Abbas; Hany Hussein Mousa; Reda biomy; Mohamed AbdelGhafar Hussein; Heba Mohammad Reyad; Osama Elagamy (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the effect of asthma in children on systolic and diastolic functions of the heart, and to explore the relationship between the two. Methods: The case-control study was conducted at Kafrelsheikh University Hospital, Egypt, from September 2019 to May 2022, and comprised asthmatic children of either gender aged 5-15 years and healthy controls matched for age and gender. The participants were subjected to detailed history, complete examination, spirometry evaluation and conventional and tissue Doppler echocardiography. Myocardial performance index was calculated and compared. Data was analysed using SPSS 22. Results: Of the 120 subjects, 60(50%) were cases; 33(55%) boys and 27(45%) girls with mean age 9.4±2.9 years (range: 5-15 years). The remaining 60(50%) subjects were controls; 34(56.6%) boys and 26(43.3%) girls with mean age 9.7±2.9 years (range: 5-15 years). Left ventricular dimensions, estimated pulmonary artery pressure, and right ventricular dimensions showed no significant inter-group differences (p>0.05), but right ventricular end diastolic diameter was significantly higher in the cases than the controls (p=0.046). Tissue Doppler showed that lateral annular peak Ê, Â, isovolumetric relaxation time and myocardial performance index values were significantly different between the groups (p<0.05). Conclusion: Tissue Doppler echocardiography could detect subtle right ventricular diastolic dysfunction in asthmatic children even with no clinical symptoms and normal findings on conventional echocardiography. Keywords: Pulmonary artery, Echocardiography, Doppler, Asthma, Spirometry